ANALISIS FAKTOR LATAR BELAKANG BUDAYA, PENGETAHUAN, DAN PENGALAMAN IBU DENGAN KEYAKINAN IBU DALAM MEMBERIKAN STIMULASI TUMBUH KEMBANG ANAK BERDASARKAN TEORI HEALTH BELIEF MODEL - ULVA NOVIANA; HENI EKAWATI (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
Belief is a belief in something that causes certain behavior. Ideally, mothers have high confidence in providing stimulation, which is an activity that stimulates the basic abilities of children aged 0-6 years, so that children grow and develop. Based on the results of a preliminary study conducted at Al Hidayah Kindergarten, Bangkalan Regency using a confidence questionnaire to 10 mothers, it was found that 5 (50%) mothers had low confidence in the stimulation of growth and development. This study aims to analyze the relationship between mother's cultural background, knowledge, experience and mother's belief in stimulating child growth and development. The research design was analytic with a retrospective study approach. The independent variables are the mother's cultural background, knowledge and experience. The dependent variable is the mother's belief. The population is 32 respondents and the sample is 30 respondents. Using probability samples method by simple random sampling. The research instrument used a questionnaire measuring instrument. Statistical test using spearman rank with = 0.05. This research has conducted an ethical feasibility test with No: 908/KEPK/STIKES- NHM/EC/III/2021 The results of statistical tests with the Spearman rank test p-value of 0.023, which means that there is a relationship between cultural background and mother's beliefs. The results of the statistical test with the Spearman rank test p-value 0.000, which means that there is a relationship between Knowledge and Mother's belief. The results of statistical tests with the Spearman rank test p-value 0.000, which means that there is a relationship between experience and mother's belief. The results of this study are expected to be able to increase mother's confidence through increased knowledge by actively seeking information through health education, and mothers to be more selective in choosing positive experiences and cultural backgrounds in increasing mother's confidence in providing growth and development stimulation.